Los cíclidos (Pisces: Pereiformes) de la Laguna de Términos y sus afluentes - Toral Almazán, Silvia; Reséndez Medina, Andrés (Revista de Biología Tropical, 1973)
Of the 283 cichlids collected between 1970 and 1973 in and around Laguna de Términos, Campeche, México, nine species (25% of the total cichlid fauna of Mcxico) have presently been identified. Identification is based on meristic and morphologic characteristics and on color patterns. The hydrologic basin of the Río Usumacinta is one of the richest in cichlid populations which retain the primitive characteristics of tbe family: Petenia splendida, Cichlasoma meeki, C. aurcum, and C. pearsei. Cichlasoma fenestratum is curyhaline but restricted to tbe rivers and streams. On the other hand, C. urophthalmus appears to be better adapted to the marine conditions wbich occur along the coast of the Isla del Carmen Lagoon. It is also found athough less frequently, in fresh water, an indication tbat it can tolerate a wide range of chlorinity.